Can Non-Traditional Predictor Variables (Academic Comfort, Study Habits/Attitudes, and Perceptual Modality Preference) Enhance the Discrimination of Academically Successful and Non-Successful Athletes: A Research Proposal - Arnett, Lynn A.; McElroy, Lee A. (My University, 1987)
This article emphasized the importance of broadening the theoretical domain of variables used to predict college athlete's academic success to include salient individual factors (beyond aptitude and achievement measures) as well as institutional factors which may influence college performance. Moreover, the authors urge the adoption of an interactive perspective in developing a suitable model of academic performance in higher education. Also included is the description of a proposed study of the possibility of improving the predictability of the student-athlete's academic success at the University of Houston by comparing the predictive power of traditional academic criteria with the predictive power of a battery of measures that includes both the traditional academic predictors and three non-traditional predictor variables (academic comfort, study habits/attitudes, and preferred perceptual modality). The purpose of the study was to identify a discriminant function by which the probability of long-term academic retention of student-athletes can be predicted at this university.
Keywords: models; academic predictors; academic performance